Migracja chłopów polskich z Królestwa Polskiego na Syberię po reformie agrarnej Piotra Stołypina - Leończyk, Sergiusz (Studia Europaea Gnesnensia, 2012)
The article addresses the issue of migration of polish populace to Siberia in the 19th century, mainly from the kingdom and Galicia. The analysis is based on Russian archive material and the papers of the kingdom of Poland.